Transparência pública no Brasil: as tecnologias de informação e comunicação como possíveis ferramentas de controle social dos gastos públicos - Cruz, Renata Leite da Silva (2020)
This research aims to investigate the potential of the tools for social control of public spending, resulting from the use of information and communication technologies, especially on the internet, with no return of the time of one year, which occurred between January 2019 and January 2020. Based on the hypothesis that, from the regulation of the Access to Information Law that came into force in 2012, which ensured the fundamental right of access to information and determined prerogatives of transparency through the use of electronic mechanisms to enable access to public information, this regulation found gaps as to the concretization and instrumentalization of that access. Thus, social control applications become essential to assist the monitoring and inspection of public spending, creating a sphere of accountability. In addition, due to the increasing insertion of technology in society, the objective was to answer the following question: what are the legal and social implications of using information and communication technologies as an open data management tool made available through LAI with a view to social control of public spending? The theoretical framework of this study was composed by the works of Guillermo O'Donnell with regard to the study of accountability, as well as the concepts developed by Manuel Castells about network society and the concepts of social control and democratic participation. Leonardo Avritzer's conceptions. To answer the research problem, the hypothetical-deductive approach method and the monographic method and procedure were chosen. Together, bibliographic and documentary research techniques were used and, at the end, direct and non-participatory observation of the selected digital social control tools. With the analysis, the relevance of these forms of social control of public expenditures was verified for the expansion of the citizen's engagement with the political sphere, since these tools enable the right of access to information from open data required by the Access to Information Law. Information making them clearer and more understandable. As for accountability, these tools presented detailed information on expenses incurred by parliamentarians, finally, with regard to the exercise of the power of denunciation, only one tool made this possibility feasible, since it presented an interface for monitoring and collecting suspicious expenses. It was concluded that, the digital tools of social control, made open data more explicit and clear, however, it was noted that the power of denunciation depends, essentially, on the citizen's interest / motivation for the exercise of citizenship through a digital activism, in addition to information sharing and monitoring.